Synthesis and Applications of Group 4 and 13 Metal-Organic Frameworks - Housley, Claire (2022)
Metal-organic frameworks (MOFs) are a class of crystalline porous materials that have received growing interest due to their highly tuneable properties and ability to form from a wide variety of components. By altering the metal centres and organic ligands used in their synthesis a vast number of structures have been developed, finding applications in gas storage, catalysis, and chemical separations. In order to be applied to these real-world challenges MOFs must possess mechanical, thermal and chemical stability. Due to the high stability associated with MOFs containing high-valent metals, this thesis focuses on the synthesis of MOFs containing Al(III), Ti(IV), Zr(IV), and Hf(IV). Throughout this thesis, reaction conditions were tailored carefully to produce new phases, increase yields, and improve crystallinity. Chapter 3 focuses on the synthesis of MOFs that could be used to remove Cu(II) ions from aqueous environments. As MOFs containing Lewis basic groups often provide good uptake of heavy metals, a series of MOFs was chosen where pendant Lewis basic groups could be added to the linker with the aim that this would increase Cu(II) uptake. MIL-53(Al), MIL-53(Al)-NH2 and MIL-121 were all synthesised using microwave heating which significantly reduced the reaction time required. Investigations into the reaction conditions used to produce MIL-53(Al)-NH2 meant that improvements on previously reported methods were made; using a mixed solvent system of DMF and H2O produced a material with no linker trapped in the pores before activation had been carried out. To the best of my knowledge, the microwave synthesis of MIL-121 was carried out for the first time. The activation of MIL-121, on the other hand, presented some challenges, with neither calcination nor Soxhlet extraction successfully removing the linker from the pores. As the stability of these materials is extremely important for their successful application as Cu(II) sorbents, the three MOFs were submerged in a range of aqueous solution at different pHs and changes in their structure were observed via PXRD analysis. MIL-53(Al) and MIL-53(Al)-NH2 were very susceptible to phase change, bringing into question their ability to act as sorbents in real world scenarios. Indeed, when Cu(II) sorption experiments were carried out, MIL-53(Al) and MIL-53(Al)-NH2 adsorbed little Cu(II). Although MIL-121 was comparatively more stable over a range of pH, it also exhibited very poor Cu(II) uptake, but this was likely due its activation being unsuccessful, resulting in the MIL-121 having a low internal surface area. The focus in Chapter 4 shifts to focus on the synthesis of Group 4 naphthalene diimide (NDI) MOFs. NDIs are a class of aromatic compounds that possess an electron deficient and redox-active core. They have a rigid, linear structure and chemical robustness that makes them ideal candidates as linkers in MOFs. There are limited examples of Group IV NDI MOFs in the literature and those that have been reported often lack crystallinity and structure solution is often performed using PXRD studies, rather than analysis of single crystals. By performing carrying out a large number of experiments where conditions such as solvent, reaction temperature, reactant ratios and the use of modulators were varied, four new frameworks were produced. Two MOFs (Zr-SA-NDI-α and Zr-SA-NDI-β) containing Zr(IV) and salicylic naphthalene diimide (SA-NDI) were produced by employing different ratios of ZrCl4 to SA-NDI and different modulators; Zr-SA-NDI-α was produced when a 1:4 metal salt to linker ratio and trifluoroacetic acid was used, whilst Zr-SA-NDI-β was produced when a 1:6 metal salt to linker ratio and benzoic acid was used. The structure of Zr-SA-NDI-α was found using single crystal X-ray diffraction, whilst the structure of Zr-SA-NDI-β remains unknown as single crystals could not be produced. Whilst different reaction conditions were being investigated in attempts to make Zr SA-NDI MOFs, a hydrogen-bonded organic framework (HOF) was also synthesised. Using a DEF/MeCN solvent mixture led to the production of single crystals of SA-NDI HOF. Single crystal X-ray diffraction revealed that the structure is held together through hydrogen bonding of adjacent SA-NDI moieties and that MeCN molecules are present in the pores of the HOF.